Pengaruh Citra Destinasi dan Fasilitas Wisata Terhadap Kepuasan Wisatawan dan Loyalitas Wisatawan pada Pantai Lon Malang Kabupaten Sampang - Wati, Erna; Wantara, Pribanus (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to determine the influence of destination image and the quality of tourist facilities on the level of satisfaction and loyalty of visitors to Lon Malang Beach, Sampang Regency. The approach used in this research is a quantitative method involving 100 respondents selected through a purposive sampling technique. Data was obtained by distributing questionnaires, and data analysis was carried out using the Partial Least Squares (PLS) method supported by SmartPLS 4 software. The findings from this research show that destination image has a significant influence on visitor satisfaction, apart from that the quality of tourism facilities also makes a big contribution. to that satisfaction. In addition, destination image is proven to have a significant influence on tourist loyalty, while tourist facilities do not show a significant influence on visitor loyalty. The level of visitor satisfaction is also proven to have a big influence on their loyalty to return visits. Overall, destination image and tourist facilities play an important role in influencing tourist satisfaction and loyalty at Lon Malang Beach, Sampang Regency. Although the influence of each variable varies depending on the route being tested. However, the level of tourist satisfaction has the greatest influence on their loyalty